An empirical analysis of the relationship between bank credit and economic growth - Vasconcelos, Marcos Roberto (2021)
This paper tests the hypothesis that bank credit is necessary for economic growth, depending on the country's level of economic and financial development. It also seeks to verify whether the relationship between financial development and economic growth is monotonic. For this, Granger's causality methodology is used for panel data, with data from 106 countries for the period between 1970 and 2016. It is observed that there was an expansion of world credit above the economic growth observed over the studied period. The main empirical findings indicate that, in general, credit causes economic growth and vice versa, in addition to verifying the non-monotonicity of the relationship between financial development and economic growth, so that, for very low credit / GDP indices, the causality of the credit to GDP is not verified.